2015
DOI: 10.1089/scd.2014.0051
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-17 Members that TargetBmpr2Influence Signaling Mechanisms Important for Embryonic Stem Cell Differentiation In Vitro and Gastrulation in Embryos

Abstract: Body axes and germ layers evolve at gastrulation, and in mammals are driven by many genes; however, what orchestrates the genetic pathways during gastrulation remains elusive. Previously, we presented evidence that microRNA-17 (miRNA-17) family members, miR-17-5p, miR-20a, miR-93, and miR-106a were differentially expressed in mouse embryos and functioned to control differentiation of the stem cell population. Here, we identify function(s) that these miRNAs have during gastrulation. Fluorescent in situ hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 87 publications
0
16
0
1
Order By: Relevance
“…It was demonstrated that hsa‐let‐7b‐5p suppressed the osteogenic differentiation capacity of stem cells (Wang et al, ). hsa‐miR‐17‐3p also influenced bone metabolism through the suppression of BMPR2 (Larabee, Coia, Jones, Cheung, & Gallicano, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that hsa‐let‐7b‐5p suppressed the osteogenic differentiation capacity of stem cells (Wang et al, ). hsa‐miR‐17‐3p also influenced bone metabolism through the suppression of BMPR2 (Larabee, Coia, Jones, Cheung, & Gallicano, ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are non-coding RNAs that regulate many biological processes, including embryonic development [3942]. miRNAs play an important role in the maternal-conceptus interface[43].…”
Section: Discussionmentioning
confidence: 99%
“…In general, one gene can be repressed by multiple miRNAs and one miRNA may repress multiple target genes, which results in the establishment of complex regulatory feedback loops . In multiple cellular processes, including development, proliferation, and differentiation, miRNAs fine‐tune cellular fate by targeting important transcription factors or key pathways .…”
Section: Introductionmentioning
confidence: 99%